With a “Licence to Adapt”: Translation Shifts in Subsidiary Corporate Value Statements - Schrøder, Victoria Susanne Nydegger (HERMES - Journal of Language and Communication in Business, 2022)
When organisations implement corporate values as a managerial tool, the Corporate Value Statement (CVS) is a central piece of corporate communication. Nevertheless, little research has been done on the linguistic aspect of the CVS in international settings. In this article, I study the case of Keolis, a French multinational corporation that empowers subsidiaries to translate and adapt the Group’s CVS to local business contexts, resulting in radically rewritten subsidiary versions. I propose a linguistic and discourse analytical approach to identify translation shifts between the headquarters’ CVS in English, and local versions in Denmark and in India. I also investigate which contextual and cultural factors may have contributed to these shifts. Findings suggest that subsidiaries use the value terms as vessels to be filled with corporate content of their choice. Contributing to a translatorial turn in international business and organisation studies, this paper illustrates how applied linguistics may inform management practice.